Correction: Treatment Landscape and Prognosis After Treatment with Trastuzumab Emtansine. - Laakmann, Elena; Emons, Julius; Taran, Florin-Andrei; Janni, Wolfgang; Uhrig, Sabrina; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Haeberle, Lothar; Ettl, Johannes; Lueftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2020)
[This corrects the article DOI: 10.1055/a-1286-2917.].
EVALuna2:382318